RANCANG BANGUN SISTEM APLIKASI GAME KUIS SEPAK BOLA BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - It has been in the know in this era of globalization, the development of technology is growing rapidly. So that development is much faster than the technology is increasingly demanded for the following development. Moreover gadgedt technology is not only used as a tool to facilitate communication, but also as a medium of entertainment, such as the internet, listening to music and one of the most entertainment to provide entertainment for the gadgedt users when playing games. So the android-based application that will provide convenience in entertainment or komunikai. This study makes an application system football quiz game based on the android so the questions are given in this application question regarding all aspects of the football world that can be used to help provide entertainment gadgedt speed-users who are mobile. System football quiz game application is built using the Java programming language using the Android Developer Tools. As for the sqlite database used is that a package of public-domain software that provides a relational database management system, or RDBMS. This study resulted in a football quiz game application that provides matter - a matter taken from various news onlain or books about the world sepab on the ball. Keywords: football quiz game android Abstraks - Telah di ketahui di era globalisasi ini, perkembangan teknologi sangat berkembang pesat. Sehingga Perkembangannya lebih cepat dari teknologi yang semakin menuntut untuk orang mengikuti perkembangannya. Apalagi Teknologi gadgedt tidak hanya digunakan sebagai alat untuk mempermudah komunikasi saja, tetapi juga sebagai media hiburan, seperti internet, mendengarkan musik dan salah satu hiburan yang paling memberikan hiburan bagi pengguna gadgedt tersebut di saat bermain game. Sehingga aplikasi yang berbasis android akan memberikan kemudahan dalam hiburan ataupun komunikai. Penelitian ini membuat sistem aplikasi game kuis sepak bola yang berbasis android sehingga di dalam soal-soal yang di berikan dalam pertanyaan aplikasi ini mengenai semua aspek yang berkaitan tentang dunia sepak bola agar bisa digunakan untuk membantu memberikan hiburan panggi pengguna gadgedt yang bersifat mobile. Sistem aplikasi game kuis sepak bola ini dibuat dengan menggunakan bahasa pemrograman Java dengan menggunakan Android Developer Tools. Sedangkan untuk database yang digunakan adalah sqlite yang merupakan paket perangkat lunak public-domain yang menyediakan relational database management system, atau RDBMS. Penelitian ini menghasilkan aplikasi Game kuis sepak bola yang menyediakan soal – soal yang diambil dari berbagai berita onlaine maupun buku yang mengenai tentang dunia sepab bola. Kata Kunci: game kuis sepak bola a